2019
DOI: 10.29298/rmcf.v10i52.398
|View full text |Cite
|
Sign up to set email alerts
|

Propiedades del suelo y nitrógeno como indicadores del crecimiento en plantaciones comerciales de teca

Abstract: La teca es una especie importante en los mercados forestales, debido al valor de su madera, lo cual en México ha incrementado el interés de establecer plantaciones. Sin embargo, la influencia de las propiedades del suelo y nitrógeno bajo esas condiciones han sido poco evaluadas. El objetivo del presente estudio fue medir la calidad del suelo en plantaciones comerciales de teca en Nayarit, México. Antes de plantar (30 días), se aplicaron fertilizantes 50 – 120 - 75 (NPK), 3 t ha-1 de hidróxido de Ca, 250 kg ha-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
1
0
0
4
Order By: Relevance
“…In general, lime elevates pH in soil and improved available macronutrient concentrations in soil solution, such as P and K while it also enhances other physical, chemical and biological properties (Bolan et al, 2003). Also, research has shown that soils with higher pH (near alkalinity) and OM were correlated with higher growth and productivity in teak (Salcedo-Pérez et al, 2019), which partly agrees with the best treatments that were when lime and organic fertilizer were added. Addition of organic amendments tend to improve overall soil fertility conditions because organic matter in soil is related to soil fertility, aggregation, nutrient retention capacity and productivity (Eden et al, 2017).…”
Section: Resultssupporting
confidence: 54%
“…In general, lime elevates pH in soil and improved available macronutrient concentrations in soil solution, such as P and K while it also enhances other physical, chemical and biological properties (Bolan et al, 2003). Also, research has shown that soils with higher pH (near alkalinity) and OM were correlated with higher growth and productivity in teak (Salcedo-Pérez et al, 2019), which partly agrees with the best treatments that were when lime and organic fertilizer were added. Addition of organic amendments tend to improve overall soil fertility conditions because organic matter in soil is related to soil fertility, aggregation, nutrient retention capacity and productivity (Eden et al, 2017).…”
Section: Resultssupporting
confidence: 54%
“…Para determinar las características físico-químicas del suelo, se extrajeron cinco sub-muestras de cada parcela, se distribuyeron con base en un muestreo diagonal de acuerdo con los puntos cardinales N, S, E y W y una al centro de la parcela hasta una profundidad de 30 cm (Barrios et al, 2011;Salcedo-Pérez et al, 2019). Con las cinco sub-muestras se procedió a formar una muestra compuesta que fue mezclada homogéneamente y se dividió en cuatro partes para obtener una muestra final de 500 g, misma que fue rotulada con datos de identificación (Salcedo-Pérez et al, 2014).…”
Section: Datos Edáficos Y Topográficosunclassified
“…Con las cinco sub-muestras se procedió a formar una muestra compuesta que fue mezclada homogéneamente y se dividió en cuatro partes para obtener una muestra final de 500 g, misma que fue rotulada con datos de identificación (Salcedo-Pérez et al, 2014). Las características físicas analizadas de cada muestra fueron: clase textural, punto de saturación, capacidad de campo, punto de marchitez permanente, conductividad hidráulica, y densidad aparente, con base en los métodos descritos por la NOM-021-RECNAT-2000 (Secretaría del Medio Ambiente y Recursos Naturales [Semarnat], 2002;Salcedo-Pérez et al, 2019).…”
Section: Datos Edáficos Y Topográficosunclassified
See 2 more Smart Citations